DISKRIMINASI GENDER DALAM PERKAWINAN KETURUNAN SAYYID DI KABUPATEN TAKALAR SULAWESI SELATAN - Mukramin, Sam'un; Salsabila, Siti Syalwa (Jurnal Studi Gender dan Anak, 2024)
Descendants of Sayyid in Islamic communities are often expected to uphold family dignity by marrying partners from the same or higher social background. Marriages involving Sayyid descendants are perceived to hold high social status due to their lineage tracing back to the Prophet Muhammad. However, such marriages are also marked by significant gender inequality. This study aims to uncover gender disparities in the marriages of Sayyid descendants in Cikoang Village, Takalar Regency, and explore alternatives to minimize gender discrimination by ensuring the freedom of partner choice is not restricted by gender or tradition. This qualitative study employs a case study approach involving three primary informants, with additional informants selected through snowball sampling. Data were collected from both primary and secondary sources. The findings reveal that: 1) Sayyid descendants occupy the highest social status in Cikoang society; 2) Female Sayyid (Syarifah) are prohibited from marrying outside the Sayyid lineage, while male Sayyid (Habaib) are free to choose partners from outside the Sayyid lineage; 3) Traditional beliefs still support marriages between Sayyid descendants or with individuals closely related to the Prophet's family; and 4) Sayyid wedding ceremonies are often marked by unique customs, such as special first-night rituals and the use of traditional clothing, with religious elements (prayers and dhikr) deeply embedded in every stage of the wedding process. This study suggests that the right to freely choose a partner, especially for female Sayyid, should be more respected to reduce gender inequality in Sayyid marriages. Keywords:  Gender discrimination, Kafaah, Syarifah, Arab descent, Choosing a spouse Abstrak Keturunan Sayyid dalam masyarakat Islam sering kali diidealkan untuk menjaga martabat keluarga dengan menikahi pasangan dari latar belakang sosial yang setara atau lebih tinggi. Perkawinan keturunan Sayyid dianggap memiliki status sosial yang tinggi karena terkait dengan silsilah Nabi Muhammad SAW. Namun, praktik perkawinan ini juga diwarnai oleh ketimpangan gender yang signifikan. Penelitian ini bertujuan untuk mengungkap ketimpangan gender dalam perkawinan keturunan Sayyid di Desa Cikoang, Kabupaten Takalar, serta mengeksplorasi alternatif untuk meminimalisir diskriminasi gender dalam konteks adat dan tradisi yang mengikat. Penelitian kualitatif ini menggunakan pendekatan studi kasus dengan melibatkan tiga informan utama, yang diperluas melalui teknik snowball sampling. Data diperoleh dari sumber primer dan sekunder. Hasil penelitian menunjukkan bahwa: 1) Status sosial keturunan Sayyid menduduki posisi tertinggi di masyarakat Cikoang; 2) Perempuan Sayyid (Syarifah) tidak diperbolehkan menikah dengan individu di luar garis keturunan Sayyid, sementara laki-laki Sayyid (Habaib) memiliki kebebasan memilih pasangan dari luar keturunan Sayyid; 3) Keyakinan tradisional masih mendukung perkawinan antar-Sayyid atau dengan individu yang memiliki hubungan dekat dengan keluarga Nabi; dan 4) Upacara perkawinan Sayyid diwarnai oleh adat istiadat khusus, seperti ritual malam pertama dan penggunaan pakaian adat, dengan unsur religius yang kuat dalam setiap tahapan acara. Penelitian ini menyarankan agar hak kebebasan memilih pasangan, terutama bagi perempuan Sayyid, lebih dihormati untuk mengurangi ketimpangan gender dalam perkawinan keturunan Sayyid. Kata Kunci:  Diskriminasi Gender, Kafaah, Syarifah, Keturunan Arab, Memilih pasangan.